E-Government-Based Innovation in Improving the Quality of Population Administration Services - Sujana, Dede; Suryono, Agus; Mindarti, Lely Indah; Amin, Fadillah (Journal of Ecohumanism, 2024)
This study aims to analyze the implementation of e-Government-based innovation diffusion in enhancing the quality of population administration services in Kediri Regency. The research is motivated by challenges in public service delivery, such as unequal access, suboptimal utilization of information technology, and the need for sustainable innovation. The study adopts the theoretical frameworks of public service, e-Government, and innovation diffusion to examine programs like SAHAJA Online and SAHAJA Keliling. The findings reveal that these innovations have improved service efficiency, though challenges persist, including limited infrastructure, insufficient outreach, and a lack of human resource capacity. The study recommends strengthening outreach programs, developing digital infrastructure, and enhancing human resource capacity to ensure the sustainability of technology-based public service innovations.